Patterns of sequence divergence and evolution of the S1 Orthologous regions between Asian and African cultivated rice species - Guyot, R.; Garavito, A; Gavory, F; Samain, S; Tohme, Joseph M.; Ghesquière, Alain; Lorieux, Mathias (Public Library of Science, 2011)
A strong postzygotic reproductive barrier separates the recently diverged Asian and African cultivated rice species, Oryza sativa and O. glaberrima. Recently a model of genetic incompatibilities between three adjacent loci: S1A, S1 and S1B (called together the S1 regions) interacting epistatically, was postulated to cause the allelic elimination of female gametes in interspecific hybrids. Two candidate factors for the S1 locus (including a putative F-box gene) were proposed, but candidates for S1A and S1B remained undetermined. Here, to better understand the basis of the evolution of regions involved in reproductive isolation, we studied the genic and structural changes accumulated in the S1 regions between orthologous sequences. First, we established an 813 kb genomic sequence in O. glaberrima, covering completely the S1A, S1 and the majority of the S1B regions, and compared it with the orthologous regions of O. sativa. An overall strong structural conservation was observed, with the exception of three isolated regions of disturbed collinearity: (1) a local invasion of transposable elements around a putative F-box gene within S1, (2) the multiple duplication and subsequent divergence of the same F-box gene within S1A, (3) an interspecific chromosomal inversion in S1B, which restricts recombination in our O. sativa×O. glaberrima crosses. Beside these few structural variations, a uniform conservative pattern of coding sequence divergence was found all along the S1 regions. Hence, the S1 regions have undergone no drastic variation in their recent divergence and evolution between O. sativa and O. glaberrima, suggesting that a small accumulation of genic changes, following a Bateson-Dobzhansky-Muller (BDM) model, might be involved in the establishment of the sterility barrier. In this context, genetic incompatibilities involving the duplicated F-box genes as putative candidates, and a possible strengthening step involving the chromosomal inversion might participate to the reproductive barrier between Asian and African rice species.